A METHOD OF PD CONTROL FOR BALANCING A UNICYCLE ROBOT - Van Dong Hai Nguyen; Thanh-Dong Pham; Manh-Tuan Tran; Ngoc-Bao Bui; Van-Nghia Pham; Tran-Nguyen-Vu Pham; Van-Thang Pham; Tan-Loc Nguyen (Indonesian Journal of Engineering and Science, 2023)
Unicycle is a robot that imitates a performance of a circus artist on a one-wheeled self-balancing bicycle. This research assumes that this model is equivalent to two separated popular models: a two-wheeled self-balancing robot and reaction wheeled inverted pendulum. On each model, we build a PD controller. Thence, we present a structure of PD controllers to balance this model at the equilibrium point. We also build an experimental unicycle robot for the laboratory. Our method is proven to work well based on both simulation and experiment.